Copper-catalyzed monoselective C–H amination of ferrocenes with alkylamines - Jia, Zhen-Sheng; Yue, Qiang; Li, Ya; Xu, Xue-Tao; Zhang, Kun; Shi, Bing-Feng (Beilstein Journal of Organic Chemistry, 2021)
A copper-catalyzed mono-selective C–H amination of ferrocenes assisted by 8-aminoquinoline is presented here. A range of amines, including bioactive molecules, were successfully installed to the ortho-position of ferrocene amides with high efficiency under mild conditions. A range of functionalized ferrocenes were compatible to give the aminated products in moderate to good yields. The gram-scale reaction was smoothly conducted and the directing group could be removed easily under basic conditions.
Keywords: amination; C–H activation; copper; ferrocene; mono-selectivity